Knowledge and perception on mother to child transmission of HIV/AIDS among antenatal mothers at Tribhuvan University Teaching Hospital, Kathmandu. - Kadariya, Jhalka (2006)
SUMMARY: This is a hospital based, cross-sectional, descriptive study, which was conducted in Tribhuvan University Teaching Hospital, Kathmandu. The objective of the study was to find out the knowledge and perception of antenatal mothers on Mothers to child transmission of HIV/AIDS. Methods used for information collection was interview with the antenatal mothers and tool used was structured questionnaire. Study population was pregnant women attending antenatal check up of Teaching Hospital. A total of 150 antenatal mothers were randomly selected for study. The study result showed that almost all respondents do have some information regarding HIV/AIDS. Some of the mothers were found to have misconception that they would contract HIV/AIDS by shaking hands (26%), sitting together (22%) and also by sharing clothes (20%). Majority of the respondents were aware about mothers to child transmission of HIV/AIDS. More than half (61.3%) of the respondents could mention about the preventive measures like avoiding breast feeding, taking medicine before two hours of delivery, check up while getting infection etc that helps to reduce the chances of transmitting HIV/AIDS from an infected mother to her child. Most of the respondents were found to have perception that HIV infected women should not give birth. They add, sometime if the women become pregnant with out knowing the presence of HIV in them they can give birth to that child with precaution by consulting with the doctor but they should not breast fed to their child because those who escape infection during delivery may nonetheless be infected through breast feeding. The main constraint of the study is that it covers very small area so the study could not represent the knowledge of all Nepalese mothers. Hence, adequate researches need to be done to find out the knowledge of all Nepalese women regarding mothers to child transmission Of HIV/AIDS.